ответ 4
https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cleft%20%5C%7B%20%5Cbegin%7Barray%7D%7Blcl%7D%203x%2B14%20%5Cgeq%204-x%20%5C%5C%20%5C%5C%20%5Cfrac%7B5x-1%7D%7B4%7D%20-%20%5Cfrac%7Bx-1%7D%7B2%7D%20%5Cgeq%203x-2%2C%20~%20%5CBig%20%7C%5Ctimes%204%20%5Cend%7Barray%7D%20%5Cright.%20%5C%5C%20%5C%5C%20%5C%5C%20%5C%5C%20%5Cleft%20%5C%7B%20%5Cbegin%7Barray%7D%7Blcl%7D%203x%2Bx%20%5Cgeq%204-14%20%5C%5C%20%5C%5C%20(5x-1)%20-%202(x-1)%20%5Cgeq%204(3x-2)%20%5Cend%7Barray%7D%20%5Cright.%20%5C%5C%20%5C%5C%20%5C%5C%20%5C%5C%20%5Cleft%20%5C%7B%20%5Cbegin%7Barray%7D%7Blcl%7D%204x%20%5Cgeq%20-10%20%5C%5C%20%5C%5C%205x-1%20-%202x%2B2%20%5Cgeq%2012x-8%20%5Cend%7Barray%7D%20%5Cright.
2) (6 + х)(х – 6) = х^2 - 36
3) (4в – 1)(4в + 1) = 16в^2 - 1
4) (х7 – а5)(х7 + а5) = х^14 - а^10
5) (0,3а3 + 0,2у4)(0,3а3 – 0,2у4) = 0,09а^6 - 0,04у^8
6) (х4 – в4)(х4 + в4)(х8 + в8) = х^16 - в^16
2) Упростить выражение: 1) (с + 2)(с – 2) – 4с(с - 1) = с^2 - 4 - 4с^2 + 4с = -3с^2 - 4 + 4с = -3с^2 + 4с - 4.2) (4а – 1)(4а + 1) + (9 + а)(а - 9) = 16а^2 - 1 + а^2 - 81 = 17а^2 - 82.
3) (с – 1)(6 – с) – (10 – с)(с + 10) = 6с - с^2 - 6 + с - 100 + с^2 = 7с - 106
3) Решить уравнение:1) (х + 3)(х – 3) –х(х + 4) = 0
х^2 - 9 - х^2 - 4х = 0
-9 - 4х = 0
-4х = 9
х = - 9/4
2) 3х(1 + 12х) – (6х – 1)(6х + 1) = 2,5х,
39 - 36х^2 + 1 = 5/2х
78х - 72х^2 + 2 = 5х
73х - 72х^2 + 2 = 0
-72х^2 + 73х + 2 = 0
72х^2 - 73х - 2 = 0
3) (х + 5)(х – 5) – (2х + 1)(х - 2) = 1 – х2.
х^2 - 25 - (2х^2 - 4х + х - 2) = 1 - х^2
х^2 - 25 - 2х^2 + 3х + 2 = 1 - х^2
- х^2 - 23 + 3х = 1 - х^2
- 23 + 3х = 1
3х = 24
х = 8
=√3*sin(2π/3)+sin(16π/2+π/2-π/3))=√3*sin120°+sin(8π+π/6)=
=√3*√3/2+sin(4*2πn+π/6)=3/2+sin(π/6)=3/2+1/2=4/2=2.